Effects of sulphurisation on vitamins (A, C and E) and malondialdehyde in apricots - Kamisli, Fethi; Karatas, Fikret (Wiley, 2009)
In this study, the 1.0 m H2SO4 solution was used as a sulphur source to sulphurise apricots. Apricot samples were immersed into 1.0 m H2SO4 solution at room temperature for time of 30, 60, 120, 180 and 240 min. Amounts of vitamins (A, C and E) and malondialdehyde (MDA) were determined as function of sulphurisation time and thus, sulphur content. It was determined that the optimum immersion time for sufficient sulphur content is 120 min. It is concluded that while amounts of vitamins decrease, the level of MDA increases with increasing immersion time and thus, sulphur contents.
Keywords: Antioxidant vitamins and malondialdehyde; apricot; sulphurisation